2012
DOI: 10.1111/j.1540-8159.2012.03376.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Atrial Fibrillation is Associated with a Poor Prognosis in Patients with Atrioventricular Block and Dual‐Chamber Pacemaker

Abstract: In patients with second- or third-degree AV block and DDD pacemaker, the development of persistent AF is associated with an increased risk of cardiovascular death and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Nevertheless, it should be stressed that the identification of AHRE detected by devices diagnostics with clinical AF, and their correlation with adverse events such as stroke is often problematic 26 . The same group of investigators studied 308 patients who implanted a dual‐chamber pacemaker owing to second‐ or third‐degree atrioventricular block without AF history 7 . After a 3 year follow‐up, 34 (11%) patients developed persistent AF associated with increased cardiovascular mortality as well as congestive heart failure 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be stressed that the identification of AHRE detected by devices diagnostics with clinical AF, and their correlation with adverse events such as stroke is often problematic 26 . The same group of investigators studied 308 patients who implanted a dual‐chamber pacemaker owing to second‐ or third‐degree atrioventricular block without AF history 7 . After a 3 year follow‐up, 34 (11%) patients developed persistent AF associated with increased cardiovascular mortality as well as congestive heart failure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the evidence linking second-or third-degree atrioventricular block with AF is less robust, 5 while atrial high-rate episodes (AHRE) and AF observed after the implantation of a pacemaker in these patients may be associated with new-onset heart failure/pacing-induced cardiomyopathy. 6,7 The pathophysiology of atrial remodeling is very complex, and the molecular pathways implicated in the initiation and perpetuation of AF show a high diversity and variability across different underlying substrates. 1,2,8 Inflammation and oxidative stress seem to play a significant pathophysiologic role in AF development and perpetuation.…”
Section: Introductionmentioning
confidence: 99%
“…The cited PeAF incidence after PM from previous studies varies greatly between 2% and 12%; this variability may stem from the use of different definitions of PeAF, from clinically diagnosed chronic AF to a more stringent definition of persistent AF based on continuous Holter monitoring [ 1 6 ]. The definition of PeAF used in our study (i.e., at least two consecutive positive ECGs acquired ≥7 days apart) was based on reports by Skanes et al [ 1 ], and Sweeny et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent/permanent atrial fibrillation (PeAF) is a clinically important atrial arrhythmia seen after the implantation of a permanent pacemaker (PM). It has a reported incidence ranging 2%–12% according to various definitions of PeAF [ 1 6 ]. Atrial fibrillation (AF) after PM implantation is progressive in nature [ 2 , 4 , 7 9 ], and some previous studies have reported that prolonged duration of AF after PM is associated with increased risk of mortality, stroke, or systemic embolism [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation